Analysis of Differentiated Instruction to Optimize Students’ Motivation in IPAS Learning - Fitri Sarabunis; Marwan Marwan; Rahmi Novalita (SAINTIS Publishing, 2025)
Learning in IPAS at the elementary school level still faces challenges in accommodating students’ diverse characteristics, which often affects learning engagement and motivation. This study aims to analyze the implementation of differentiated instruction and to describe students’ learning motivation in IPAS learning on the topic “My Responsibility in Social Interaction”. This research employed a qualitative approach with an intrinsic case study design. Data were collected through in-depth interviews with teachers, classroom observations, and document analysis, and were analyzed using NVivo software. The findings indicate that differentiated instruction was implemented through the identification of students’ readiness, interests, and learning styles, as well as through differentiation of content, process, and product. The implementation of differentiated instruction had a positive impact on students’ learning motivation, as reflected in increased active participation, enthusiasm, confidence, and willingness to ask questions. The study concludes that differentiated instruction is a relevant and effective approach to improving the quality of IPAS learning in elementary schools.